Effect of chlorogenic acid supplementation in MPTP-intoxicated mouse - Singh, S.S.; Birla, H.; Zahra, W.; Kumar, G.; Gedda, M.R.; Tiwari, N.; Patnaik, R.; Singh, R.K.; Singh, S.P. (Frontiers Media S.A., 2018)
Oxidative stress and neuroinflammation play a key role in dopaminergic (DA) neuronal degeneration, which results in the hindrance of normal ongoing biological processes in the case of Parkinson's disease. As shown in several studies, on 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) administration, different behavioral parameters have suggested motor impairment and damage of antioxidant defence. Thus, some specific biological molecules found in medicinal plants can be used to inhibit the DA neuronal degeneration through their antioxidant and anti-inflammatory activities. With this objective, we studied chlorogenic acid (CGA), a naturally occurring polyphenolic compound, for its antioxidant and anti-inflammatory properties in MPTP-intoxicated mice. We observed significant reoccurrence of motor coordination and antioxidant defence on CGA supplementation, which has been in contrast with MPTP-injected mice. Moreover, in the case of CGA-treated mice, the enhanced expression of tyrosine hydroxylase (TH) within the nigrostriatal region has supported its beneficial effect. The activation of glial cells and oxidative stress levels were also estimated using inducible nitric oxide synthase (iNOS) and glial fibrillary acidic protein (GFAP) immunoreactivity within substantia nigra (SN) and striatum of MPTP-injected mice. Administration of CGA has prevented the neuroinflammation in SN by regulating the nuclear factor-κB expression in the MPTP-induced group. The significant release of certain pro-inflammatory mediators such as tumor necrosis factor-α and interleukin (IL)-1β has also been inhibited by CGA with the enhanced expression of anti-inflammatory cytokine IL-10. Moreover, reduced GFAP staining within the nigrostriatal region has supported the fact that CGA has significantly helped in the attenuation of astrocyte activation. Hence, our study has shown that CGA supplementation shows its therapeutic ability by reducing the oxidative stress and neuroinflammation in MPTP-intoxicated mice. © 2018 Singh, Rai, Birla, Zahra, Kumar, Gedda, Tiwari, Patnaik, Singh and Singh.
Keywords: Chlorogenic acid; Dopaminergic neuron; Neuroinflammation; Oxidative stress; Parkinson's disease; Substantia nigra